Bioleaching of uranium from ores and rocks using filamentous fungi - Bhatti, Tariq M.; Tuovinen, Olli H. (Frontiers in Microbiology, 2025)
The purpose of this article is to review the role of filamentous fungi in the leaching of uranium from ores and rocks. Fungi produce short-chain fatty acids through the fermentation and partial oxidation of organic compounds. Biomass can be separated from the culture, while organic acids in spent media dissolve and sequester uranium from minerals in ores and rocks. Oxide, carbonate, and silicate ores containing hexavalent uranium are suitable for this treatment. Fungi can maximize the production of short-chain fatty acids. Uranium dissolution and sequestration are attributed mostly to the formation of soluble U(VI)-carboxylate complexes with citric and oxalic acids, although other carboxylic acids can also sequester uranium. The leach solutions maintain a pH level between 1.5 and 3.5, as the low pH facilitates proton attack on the minerals and minimizes the precipitation of metals in the leach solution. Two types of uranium leaching processes using fungi have been tested: one-step leaching, where biomass is not separated before contact with the uranium mineral, and two-step leaching, which employs spent medium after the removal of fungal biomass. Process optimization to the pilot stage has not yet been reported in the literature. To date, this article is the first to review the role of filamentous fungi in uranium bioleaching from ores and rocks.